Assessment of qualitative enrichment of organic paper mill wastes through vermicomposting: humification factor and time of maturity. Issue 5 (May 2019) - Ganguly, Ram Kumar; Chakraborty, Susanta Kumar
Abstract: The process of bioconversion of solid organic wastes through vermicomposting justifies the environmental message for sustainability such as reduce, recycle and reuse of wastes. In the present study, wastes derived from two different types of paper mill sludge (primary and secondary), was used for their bioconversion through the vermicomposting process using an indigenous species of earthworm ( Perionyx excavatus). The maturity and stability stage of vermicompost production was assessed using FT-IR, GC-MS and TG analyses. During vermicomposting, different biochemical functional groups present in the wastes have shown differential chemical alteration and turnover as revealed by FT-IR spectroscopy. This study has also confirmed the trend of biodegradation of complex substances like lignin, cellulose, proteins etc. and thereby demonstrates the extent of mineralization. TG spectral analysis had revealed a mass loss of 80% and 71% in vermicompost produced from primary and secondary sludge respectively. GC-MS studies have also shown the presence of several humic acids like octadecanoic acid, heptadecanoic acid etc. in the decomposing substances demonstrating as an indicator of the maturity of products. This was further confirmed by the decrease of humification index which focuses the combined action of both earthworms and microbes in the degradation of organic wastes. The present study has highlighted the role of an indigenous earthworm in converting specific industrial wastes especially by recording the point of maturation using humic acids an indicator of the quality of decomposing of wastes following several instrumental applications.